On the Relationship Between Firm Size and Export Intensity - Bonaccorsi, Andrea (Journal of International Business Studies, 1992)
Export marketing literature supports the view that firm size is positively related to export intensity. Although the empirical findings have been mixed, a number of theoretical arguments are used to support this proposition, i.e., international marketing economies of scale, limited managerial and financial resources of small firms, decisionmaker's risk perception. Based on a large survey of the Italian manufacturing industry, the article falsifies the proposition and challenges some widely held assumptions in export marketing literature.